Prevalence and associated factors of smoking among male Undergraduate students in International Islamic University Malaysia - Azmi, Junainah; Syed Elias, Sharifah Munirah; Nurumal, Mohd. Said; Mohd Mokhtar, Hanida Hani (2021)
Objective: The aims of this study were to determine the prevalence and associated factors of smoking among male undergraduate students in International Islamic University Malaysia. Methods: A cross-sectional survey was done on 552 samples of male undergraduate students of International Islamic University Malaysia, using a set of questionnaire and further verification of breath carbon monoxide (CO) level using PiCO Smokerlyzer was done. Questions concerned socio-demographic variables, religiosity level, and nicotine addiction level for smokers. Data entry and analysis were done using SPSS version 25 and were presented in descriptive statistics, chi-square, and logistic regression test results. Results: The overall prevalence of smokers was 12%. The most demanding reason for smoking was stress (47%) followed by peer pressure (31.8%). In multiple logistic regression, significant predictors of smoking in the model were study background (p = 0.020) and religiosity level (p = 0.001). Conclusion: The findings provide baseline data to develop a new cessation program to overcome smoking problem at the university level for future tobacco control strategy.